Alberta Giménez y Adrove, an avant-garde pedagogue woman (Journal of Parents and Teachers, 2017)
The academic training of women teachers in the Balearic Islands, as well as the pedagogical innovation introduced by Alberta Giménez in the Real Colegio de la Pureza, portrays her as a true pioneer of early 20th century education. The article shows the most relevant biographical data of Alberta Giménez, while describing how a pedagogical tradition was shaped, according to the albertian charism, from its beginnings to the present day.
Keywords: Alberta Giménez; pedagogy; training of women teachers; education; Mallorca; School of Teaching; Colegio Pureza de María; albertian charism